Technology, Productivity and the Multinational Enterprise - Ostry, Sylvia (Journal of International Business Studies, 1998)
This article reviews the relevance of the transactions-costs model to the role of the firm in production and diffusion of knowledge. A revival of interest in technology, productivity and growth has generated a new empirical and theoretical literature. A review of these developments suggests that they have not yet been reflected in significant adaptation of the conventional firm-versus-market concept. Research has been severely hampered by data gaps and suggestions are made with respect to improvements in the information base. Finally technology issues are and will be of increasing significance in both domestic and international policy, and must be factored into the conceptual template of corporate strategy.